2021
DOI: 10.26522/brocked.v30i2.866
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing the shift: How postsecondary contract and continuing faculty moved to online course delivery

Abstract: The shift to online learning that occurred in March of 2020, created an unprecedented period of intense work for faculty and sessional instructors at the post-secondary level. This shift necessitated courses be adapted under short timelines, new technology be integrated into course design and teaching strategies and assessment methods be adapted for an online environment (Van Nuland et al., 2020). This study examines how sessional instructors, referred to in this chapter as contract faculty, and continuing ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Two studies, by Watermeyer et al (2021) and Littlejohn et al (2021), investigated the experiences of university teachers in the United Kingdom as they transitioned to online teaching during the lockdown. In Canada, Danyluk and Burns (2021) surveyed full-time and contract university faculty to examine and compare their experiences during the transition. A later study by Trevisan and De Rossi (2023) examined the impacts on education faculty in Italy and the United States, a year after moving to digitized instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies, by Watermeyer et al (2021) and Littlejohn et al (2021), investigated the experiences of university teachers in the United Kingdom as they transitioned to online teaching during the lockdown. In Canada, Danyluk and Burns (2021) surveyed full-time and contract university faculty to examine and compare their experiences during the transition. A later study by Trevisan and De Rossi (2023) examined the impacts on education faculty in Italy and the United States, a year after moving to digitized instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Hodges et al (2020) and other researchers have pointed out, the sudden move to ERT in the winter of 2020 meant that university educators, including information literacy librarians, had to abruptly adapt their instructional practices and transition from the classroom to online teaching, often in just a few days (Danyluk & Burns, 2021;Khan, 2021;Littlejohn et al, 2021;Shin et al, 2022;Watermeyer et al, 2021). Hodges et al observed that this change left many educators feeling like "instructional MacGyvers, having to improvise quick solutions in less-than-ideal circumstances" (p. 3).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations